Democracy and the limits of self government - Przeworski,Adam (Cambridge, 2010)
The political institutions under which we live today evolved from a revolutionary idea that shook the world in the second part of the eighteenth century: that a people should govern itself. Yet if we judge contemporary democracies by the ideals of self-government, equality and liberty, we find that democracy is not what it was dreamt to be. This book addresses central issues in democratic theory by analyzing the sources of widespread dissatisfaction with democracies around the world. With attention throughout to historical and cross-national variations, the focus is on the generic limits of democracy in promoting equality, effective participation, control of governments by citizens, and liberty. The conclusion is that although some of this dissatisfaction has good reasons, some is based on an erroneous understanding of how democracy functions. Hence, although the analysis identifies the limits of democracy, it also points to directions for feasible reforms.
Keywords: Democracy-History